Verbo-Nominal Constructions withkommen‘come’ in German - Smirnova, Elena; Vanessa Stöber (My University, 2022)
AbstractThe paper presents the results of a diachronic study of the light verb constructions containing the German verbkommen‘come’ accompanied by a prepositional phrase containing a deverbal noun and the prepositionzu‘to’. The analysis is based on the corpus data from the DTA (DeutschesTextarchiv) between 1600 and 1900. The aim of the paper is to integrate traditional grammatical descriptions ofFunktionsverbgefügewith grammaticalization and lexicalization approaches as well as with more recent usage-based constructionist approaches. In doing so, the view of composite predicates as more or less grammaticalized or more or less lexicalized constructions will be challenged by offering empirical evidence in favor of a more diversified account. It will be argued that it is often a matter of the methodological perspective as to which particular status is assigned to a structure under investigation.